Comparison of Practice Guidelines, BRCAPRO, and Genetic Counselor Estimates to Identify Germline BRCA1 and BRCA2 Mutations in Pancreatic Cancer. Issue 4 (13th February 2018) - Grant, Robert C.; Holter, Spring; Borgida, Ayelet; Dhani, Neesha C.; Hedley, David W.; Knox, Jennifer J.; Akbari, Mohammad R.; Zogopoulos, George; Gallinger, Steven
Abstract: Germline BRCA1 and BRCA2 (BRCA) mutation carriers with pancreatic ductal adenocarcinoma (PDAC) may benefit from precision therapies and their relatives should undergo tailored cancer prevention. In this study, we compared strategies to identify BRCA carriers with PDAC. Incident cases of PDAC were prospectively recruited for BRCA sequencing. Probands were evaluated using the National Comprehensive Cancer Network (NCCN) and the Ontario Ministry of Health and Long‐Term Care (MOHLTC) guidelines. The probability of each proband carrying a mutation was estimated by surveying genetic counselors and using BRCAPRO. BRCA mutations were detected in 22/484 (4.5%) probands. 152/484 (31.2%) and 16/484 (3.3%) probands met the NCCN and MOHLTC guidelines, respectively. The NCCN guidelines had higher sensitivity than the MOHLTC guidelines (0.864 versus 0.227, P  < 0.001) but lower specificity (0.712 versus 0.976, P  < 0.001). One hundred and nineteen genetic counselors completed the survey. Discrimination was similar between genetic counselors and BRCAPRO (area‐under‐the‐curve: 0.755 and 0.775, respectively, P  = 0.702). Genetic counselors generally overestimated ( P  = 0.008), whereas BRCAPRO severely underestimated ( P  < 0.001), the probability that each proband carried a mutation. Our results indicate that the NCCN guidelines and genetic counselors accurately identify BRCA mutations in PDAC, while the MOHLTC guidelines and BRCAPRO should be updated to account for the association between BRCA and PDAC.